Plants & People - Mauseth, James D (Jones & Bartlett Learning, 2013)
Written for the introductory course for non-science majors, Plants & People outlines the practical, economical, and environmental aspects of how plants interact with human beings and the earth. The book begins with an introduction to the fundamental concepts of plant biology, followed by sections focused on the global issues related to plants and their connection to global warming, deforestation, and biogeography. It continues by examining how plants influence our daily lives, from food and drink to clothing and medicinal usage. The text encourages readers to have a continued interest in plants in our society and to consider how our actions play a role in their existence.